La cultura organizacional en la municipalidad distrital de victor larco herrera, provincia de trujillo, en el año 2014 - Abad Farías, Juana Mercedes (2014)
In the formless present of thesis The culture is analyzed organizacional in the Municipality distrital of Víctor Larco Herrera of the Province of Trujillo in the year 2014, demonstrates across the characteristics of individualism across interests of groups and crises of institutional identity, which influence the labor performance of the own workers; It constituted stages essentially ethnographic or descriptively and simultaneously, ethnological or analytical. For the accomplishment of the fieldwork there was necessary the obtaining of information of frequent use in the social sciences like the methods and quantitative and qualitative technologies. The size of the population will be in agreement to the workers' quantity, it belonged 35 working workers, 15 employees. The investigation was beside analyzing the individualism across interests of groups, it takes form of breaches of procedure and negative attitudes I do not respect towards other workers, this one determines that the organization councillor contributes to the deficient cooperation and collective harmonic integration in the Municipality distrital of Víctor Larco Herrera of the Province of Trujillo in the year 2014. Was observed also the institutional identity related between the own workers and of his managerial commitment, there affect in the deficient participation of activities for the contributions or offers of improvement organizacional that are realized in the Municipality distrital of Víctor Larco Herrera.